Inkjet-based multilayered growth factor-releasing nanofilms for enhancing proliferation of mesenchymal stem cells in vitro - Choi, Moonhyun; Choi, Daheui; Han, Uiyoung; Hong, Jinkee (Journal of industrial and engineering chemistry (Seoul, Korea), 2017)
[Display omitted] •By inkjet based LbL assembly, fabrication of bFGF/HEP nanofilms on a flexible PET substrate.•Active bFGFs were released from printed LbL nanofilms during 3days.•Printed LbL films can contain different amounts of bFGF through control of the number of deposited layers.•With active bFGFs from nanofilms, the proliferation of rabbit BMSCs was improved. We report the preparation and characterization of inkjet-based basic fibroblast growth factor (bFGF)-containing nanofilms on a flexible PET substrate. bFGF and heparin (HEP) were assembled by inkjet-based layer-by-layer (LbL) assembly driven by electrostatic interactions. The bFGF/HEP nano-assembly surface coatings were formed via alternating printing adsorption of positively charged bFGF and negatively charged HEP; the process was monitored by UV–vis spectroscopy and quartz crystal microbalance. The bFGF release profile could be controlled by altering the number of layers of printed LbL films. Mesenchymal stem cells, which are capable of extended proliferation in vitro, require a continuous supply of bFGF for proliferation. However, enhancing mesenchymal stem cell proliferation by continuous supplying bFGF is difficult, even with medium replacement, because of the instability of bFGF. Here, we established a novel system for releasing bioactive bFGF from a modified surface by using an inkjet-based nanofilm fabrication method.